Effectiveness of Atorvastatin in Reducing Inflammatory Markers and Hospitalization Period in Adults With COVID-19: A Randomized Clinical Trial - Reihane Tabaraii; Akram Asghari; Leila jafari; Mostafa Vahedian; Mohammad Bagherzadeh; Jamshid Vafaee Manesh (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Qum, 2022)
Background and Objectives: Statins, which are primarily used for controlling blood cholesterol levels, have a well-known role in inhibiting the inflammatory process and reducing mortality rate of infectious diseases. This study aims to evaluate the effect of atorvastatin along with standard treatment protocol in hospitalized adults with COVID-19. Methods: This randomized controlled clinical trial was conducted on adults hospitalized due to COVID-19 infection at Shahid Beheshti Hospital in Qom, Iran from April to September 2020.  They were randomly divided into groups of treatment (n=37, receiving atorvastatin 40 mg daily for 30 days plus standard treatment protocol) and control (n=37, receiving standard treatment protocol alone). The data were analyzed in SPSS v.22 software using chi-square, paired t-test, and ANOVA. P<0.05 was statistically significant. Results: The CRP level in the atorvastatin-treated group decreased significantly such that there was a significant difference between the two groups after 30 days (P=0.01). There was no significant difference in Spo2 level on the discharge day. The length of hospitalization in the atorvastatin-treated group was significantly reduced compared to the control group (P<0.05). Conclusion: The use of atorvastatin as an adjunctive treatment method, can significantly reduce the length of hospitalization and CRP level after 30 days in hospitalized patients.